Anatomi dan Aktualisasi Islam Moderat di Tengah Gelombang Gerakan Islam Kontemporer di Indonesia - Zuhri, Achmad Muhibin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
The article aims to emphasize conceptually and operationally that moderate Muslims are those who reject extreme religious models and declare violence and terrorism as views and behaviours that are not justified by religion. In addition, moderate Muslim groups reject the idea of a single truth from groups or individuals who monopolize the definition of Islam and prefer to seek common ground with other faith groups rather than the spirit of difference. Amid a wave of contemporary Islamic movements in Indonesia, both political and puritanical, Islamic moderatism in Indonesia anatomically displays its actualization in various segments of life. According to this study's findings, Islam wasathiyah shows a willing, tolerant and open religious attitude and respects various views on religious, social, political and state systems aspects.